An agent-based model for improving museum design to enhance visitor experience. - Ji, Yijing (Cranfield University, 2022)
Museum experience is a multi-layered journey including ontological, sensory, intellectual, aesthetic, and social aspects. In recent years, the museum sector has faced a number of challenges in terms of the need to enhance the potential of the experience while maintaining authenticity and credibility. For public science communication in museums, exhibition is an important medium for connecting exhibits and visitors, and as such, the study of visitors' senses and behaviours under impact of various museum layout designs has become an important research direction. The purpose of this study is to explore the recall of visitors' memories in the exhibition space by integrating images, echoes and tactile senses, and then transform memories and interactions into their own experience and knowledge base. The impact of spatial design and other design elements on visitors' memories is also explored. We have conducted Agent-based simulation, by setting up virtual visitors, exhibition spaces and artefact based on real gallery spaces, as a time-saving and cost-saving method to improve exhibition interactivity and content coherence. Meanwhile, through the simulation of this novel way, visitors can observe and predict the interactive experience between visitors and the exhibition, so as to improve the curatorial team's research on tourist behaviour and spatial design scheme. Next, the simulated data on visitors' memory recall behaviour is compared with the actual observed data to explore the authenticity of visitors' behaviour in the simulated museum. The impact of this study is by integrating a variety of shared understandings between curators, exhibition management and participants, drawing on diverse information based on experience, practice and simulation. It seeks to provide future museum- oriented practitioners, particularly in small and medium-sized museum exhibition spaces, with a novel perspective and approach to observing or predicting the experience of visitors' sensory interactions within an exhibition. Furthermore, at the same time as enhancing the visitor’s exhibition experience, the content of exhibition story is fully transformed into its own knowledge accumulation.
Simon, Jude - Associate Supervisor Wiliams, Leon - Associate Supervisor
Keywords: Cognition; Human Behaviour; Museum Space; Exhibition Space; Short-Term Memory; Interior Design; Sensory Experience